Clickable and imageable multiblock polymer micelles with magnetically guided and PEG-switched targeting and release property for precise tumor theranosis. (November 2017) - Wei, Jing; Shuai, Xiaoyu; Wang, Rui; He, Xueling; Li, Yiwen; Ding, Mingming; Li, Jiehua; Tan, Hong; Fu, Qiang
Abstract: Targeted delivery of therapeutics and diagnostics using nanotechnology holds great promise to minimize the side effects of conventional chemotherapy and enable specific and real-time detection of diseases. To realize this goal, we report a clickable and imageable nanovehicle assembled from multiblock polyurethanes (MPUs). The soft segments of the polymers are based on detachable poly(ethylene glycol) (PEG) and degradable poly(ε-caprolactone) (PCL), and the hard segments are constructed from lysine- and cystine-derivatives bearing reduction-responsive disulfide linkages and click-active alkynyl moieties, allowing for post-conjugation of targeting ligands via a click chemistry. It was found that the cleavage of PEG corona bearing a pH-sensitive benzoic-imine linkage (BPEG) could act as an on-off switch, which is capable of activating the clicked targeting ligands under extracellular acidic condition, followed by triggering the core degradation and payload release within tumor cells. In combination with superparamagnetic iron oxide nanoparticles (SPION) clustered within the micellar core, the MPUs exhibit excellent magnetic resonance imaging (MRI) contrast effects and T 2 relaxation in vitro, as well as magnetically guided MR imaging and multimodal targeting of therapeutics to tumor precisely, leading to significant inhibition of cancer with minimal side effect. This work provides a safe and versatile platform for the further development of smart theranostic systems for potential magnetically-targeted and imaging-guided personalized medicine. Graphical abstract: